A Detailed Analytical Study of Non-Linear Semiconductor Device Modelling - Umesh Kumar (Active and Passive Electronic Components)
This paper presents a detailed analytical study of Gunn, SCR, and p-n junction and of the physical processes that occur inside. Based on the properties of these devices, models for Gunn, SCR, and p-n junction diode have been developed. The results of computer simulated examples have been presented in each case. The non-linear lumped model for Gunn is a unified model as it describes the diffusion effects as the-domain traves from cathode to anode. An additional feature of this model is that it describes the domain extinction and nucleation phenomena in Gunn dioder with the help of a simple timing circuit. The non-linear lumped model for SCR is general and is valid under any mode of operation in any circuit environment. The memristive circuit model for p-n junction diodes is capable of simulating realistically the diode’s dynamic behavior under reverse, forward and sinusiodal operating modes. The model uses memristor, the charge-controlled resistor to mimic various second-order effects due to conductivity modulation. It is found that both storage time and fall time of the diode can be accurately predicted.